Prototipe Pengingat Perawatan Komponen Sepeda Motor Berbasis Arduino dan SMS Gateway - Jayadi, Sukma; Fitriyadi, Fitriyadi (STMIK Banjarbaru, 2024)
Problems that arise related to negligence or forgetfulness in maintaining motorcycle components, such as oil changes, brake pads, and CVT services, can result in potential damage to engine components. This study aims to build a device that can remind users to perform maintenance on these components. The results of the study include mileage testing, service notifications, oil changes, and brake pads, as well as a tool reset system. An inductive proximity sensor is used to detect metal and display the mileage value on a 16x2 LCD. The SIM800L module functions to receive messages from mobile phones and provide reset commands to reset the tool system, including resetting the total mileage. The SIM800L module also successfully sends SMS notifications for service maintenance, oil changes, and brake pads according to the multiples of the mileage that have been determined in motorcycle maintenance.Keywords: Motorcycle Maintenance; Arduino; Inductive Proximity Sensor. AbstrakPermasalahan yang muncul terkait kelalaian atau lupa dalam merawat komponen sepeda motor, seperti penggantian oli, kampas rem, dan servis CVT, dapat mengakibatkan potensi kerusakan pada komponen mesin. Penelitian ini bertujuan membangun perangkat yang dapat mengingatkan pengguna untuk melakukan perawatan pada komponen-komponen tersebut. Hasil penelitian mencakup pengujian jarak tempuh, notifikasi servis, ganti oli, dan kampas rem, serta sistem reset alat. Sensor proximity induktif digunakan untuk mendeteksi logam dan menampilkan nilai jarak tempuh pada LCD 16x2. Modul SIM800L berfungsi untuk menerima pesan dari ponsel dan memberikan perintah reset untuk mereset sistem alat, termasuk reset total jarak tempuh. Modul SIM800L juga berhasil mengirim notifikasi SMS untuk perawatan servis, ganti oli, dan kampas rem sesuai dengan kelipatan jarak tempuh yang telah ditentukan dalam perawatan sepeda motor.